2018
DOI: 10.1111/evo.13409
|View full text |Cite
|
Sign up to set email alerts
|

Sexual imprinting and speciation between two Peromyscus species

Abstract: Sexual isolation, a reproductive barrier, can prevent interbreeding between diverging populations or species. Sexual isolation can have a clear genetic basis; however, it may also result from learned mate preferences that form via sexual imprinting. Here, we demonstrate that two sympatric species of mice-the white-footed mouse (Peromyscus leucopus) and its sister species, the cotton mouse (P. gossypinus)-hybridize only rarely in the wild despite co-occurrence in the same habitat and lack of any measurable intr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 95 publications
0
15
2
Order By: Relevance
“…While dietary information was learnable and led to some assortative mating preferences in females, male preferences appeared random with respect to diet. Although a number of other studies have found sex‐specific differences in the degree or strength of sexual imprinting (e.g., Delaney & Hoekstra, ; Kozak, Head, & Boughman, ; Verzijden et al, ; Verzijden, Korthof, & Cate, ; Witte & Sawka, ), the sex difference observed here was surprising as we previously established that both P. gossypinus males and females strongly sexually imprint on their parents in a cross‐fostering experiment with P. leucopus (Delaney & Hoekstra, ). Thus, males are capable of sexual imprinting but in this study either failed to imprint on diet, imprinted on diet but relied more heavily on other cues (e.g., visual, vocal, or chemical cues; Rosenthal, ) to select mates, or we were unable to detect this pattern due to limited sample sizes.…”
Section: Discussioncontrasting
confidence: 75%
See 4 more Smart Citations
“…While dietary information was learnable and led to some assortative mating preferences in females, male preferences appeared random with respect to diet. Although a number of other studies have found sex‐specific differences in the degree or strength of sexual imprinting (e.g., Delaney & Hoekstra, ; Kozak, Head, & Boughman, ; Verzijden et al, ; Verzijden, Korthof, & Cate, ; Witte & Sawka, ), the sex difference observed here was surprising as we previously established that both P. gossypinus males and females strongly sexually imprint on their parents in a cross‐fostering experiment with P. leucopus (Delaney & Hoekstra, ). Thus, males are capable of sexual imprinting but in this study either failed to imprint on diet, imprinted on diet but relied more heavily on other cues (e.g., visual, vocal, or chemical cues; Rosenthal, ) to select mates, or we were unable to detect this pattern due to limited sample sizes.…”
Section: Discussioncontrasting
confidence: 75%
“…To assess whether male and female choosers preferred stimuli based on their parental diet, we recorded each chooser's most preferred stimulus (defined as whichever stimulus the chooser spent more time with). We previously showed that the proportion of time a chooser spent with a stimulus in our gated mate choice apparatus near‐perfectly predicts copulation (Delaney & Hoekstra, ), allowing us to convert chooser preference to a binary variable (garlic mate preferred or orange mate preferred). Then, we used one‐sided Fisher's Exact tests to determine if preferences for garlic versus orange were significantly different between females by diet and/or between males by diet.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations